Embedded COF nanofiber aerogel material, preparation method and application

By preparing embedded COF nanofiber aerogel materials, the problems of low evaporation flux and volatile organic compound pollution of photothermal materials have been solved, achieving efficient water treatment and purification effects, and improving the efficiency and safety of solar distillation water purification technology.

CN120939860APending Publication Date: 2025-11-14ZHENGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511217740.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-28
Publication Date
2025-11-14

AI Technical Summary

Technical Problem

Existing photothermal materials have low evaporation flux, and the distillation process is susceptible to volatile organic compound pollution, affecting water quality safety.

Method used

An embedded COF nanofiber aerogel material was used to prepare a PAN/TP blended nanofiber membrane by electrospinning, and a COF@M catalyst was grown in situ within it to form a PAN/COF@M composite nanofiber membrane. Combined with freeze-drying of chitosan solution, an aerogel material with high surface area and porous structure was prepared to achieve catalytic water purification function.

Benefits of technology

It significantly increased the evaporation flux to 3.04 kg·m⁻²·h⁻¹ and was able to rapidly degrade volatile organic pollutants in wastewater, ensuring water safety and solving the problem of global freshwater scarcity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120939860A_ABST
    Figure CN120939860A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of wastewater treatment, in particular to an embedded COF nanofiber aerogel material, a preparation method and application. The PAN / COF (at) M nanofiber aerogel material with double functions is synthesized, the PAN / COF (at) M nanofiber aerogel material not only can be used as a photo-thermal material, but also can degrade different organic pollutants by selecting different metals M (Co, Ti, Zn, Fe, Cu and the like), the COF (at) M catalytic material is loaded on an electrostatic spinning PAN nanofiber membrane in situ, and a short nanofiber assembly method is adopted after homogenization, so that the photocatalytic performance of the PAN / COF (at) M nanofiber aerogel material is improved. The embedded COF nanofiber aerogel material with the three-dimensional interface evaporation capability is prepared. The embedded COF nanofiber aerogel material is a nanofiber columnar evaporator with three-dimensional interface evaporation capacity, and the three-dimensional evaporator can significantly improve the water flux by expanding an evaporation interface and utilizing environment energy for collaborative evaporation; the method has important significance on development of a solar distillation water purification technology and solving of global scarcity of fresh water resources.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of wastewater treatment technology, specifically to an embedded COF nanofiber aerogel material, its preparation method, and its application. Background Technology

[0002] Solar-powered interfacial evaporation is a low-cost and efficient clean water production technology that uses only solar energy as an energy source. It is clean and environmentally friendly and is of great significance for supplementing the world's scarce freshwater resources.

[0003] Photothermal materials are the core components of solar interfacial distillation technology. Their structure and properties directly determine the efficiency of photothermal materials. Generally, photothermal materials should meet three requirements: (1) excellent light absorption; (2) good hydrophilicity and water transport capacity; and (3) sufficient heat preservation capacity. Improving the above-mentioned capabilities of photothermal materials is the key to increasing the yield of solar interfacial distilled water.

[0004] Two-dimensional evaporators, limited by theoretical evaporation limits, produce small amounts of freshwater. Furthermore, their limited surface area leads to significant heat loss, making it difficult to integrate catalytic degradation functions. Volatile / semi-volatile organic pollutants in the water tend to accumulate at the product water end during evaporation, threatening water quality and rendering them unsuitable for current wastewater treatment methods. Therefore, this application proposes a solar interfacial evaporation photothermal material that not only solves the problem of low evaporation flux in existing photothermal materials but also effectively degrades volatile organic compounds in wastewater. This is of great significance for the development of solar distillation water purification technology and for addressing the global scarcity of freshwater resources. Summary of the Invention

[0005] The purpose of this invention is to provide an embedded COF nanofiber aerogel material, its preparation method, and its application, in order to solve the problems of low evaporation flux of existing photothermal materials and the susceptibility of the distillation process to volatile organic compound pollution.

[0006] To achieve the above objectives, the present invention adopts the following technical solution: an embedded COF nanofiber aerogel material, comprising PAN / TP electrospun nanofiber aerogel and COF@M catalyst, wherein the COF@M catalyst is uniformly loaded in the PAN / TP electrospun nanofiber aerogel.

[0007] Furthermore, in the COF@M catalyst, the metal M includes Co, Ti, Zn, Fe, and Cu.

[0008] A method for preparing embedded COF nanofiber aerogel materials includes the following steps: S1. Electrospinning to prepare PAN / TP blended nanofiber membranes; S2. The PAN / TP blended nanofiber membrane prepared in S1 is mixed and reacted with the COF precursor, and COF is grown in situ on the PAN / TP blended nanofiber membrane to obtain the PAN / COF composite nanofiber membrane. S3. React the PAN / COF composite nanofiber membrane prepared in S2 with metal ions to obtain the PAN / COF@M composite nanofiber membrane. S4. After mixing the PAN / COF@M composite nanofiber membrane obtained in S3 with the chitosan solution evenly, pour it into a mold and freeze-dry it to obtain the embedded COF nanofiber aerogel material of the present invention.

[0009] Furthermore, in S1, the preparation of the PAN / TP blend nanofiber membrane includes the following steps: a1. Dissolve polyacrylonitrile (PAN) in N,N-dimethylformamide (DMF) to obtain solution A; a2. Dissolve 2,4,6-tricarboxymethylphloroglucinol TP in N,N-dimethylformamide DMF to obtain solution B; a3. After thoroughly mixing solution A and solution B, place them in a spinning machine to spin PAN / TP blended nanofiber membranes.

[0010] Furthermore, in step S2, the preparation of the PAN / COF composite nanofiber membrane includes the following steps: b1. Mix PAN / TP film, 2,5-diaminohydroquinone hydrochloride powder, dioxane and trimethylbenzene mixed solution and acetic acid to obtain a mixture; b2. After ultrasonic treatment of the b1 mixture, place it in liquid nitrogen to remove oxygen, and then seal it under vacuum for reaction. b3. The product obtained from reaction b2 is washed sequentially with tetrahydrofuran, water, and acetone, and then dried under vacuum to obtain the PAN / COF composite nanofiber membrane.

[0011] Furthermore, in the dioxane and trimethylbenzene mixed solution, the volume ratio of dioxane to trimethylbenzene is 1:1.

[0012] Furthermore, in step S3, the preparation of the PAN / COF@M composite nanofiber membrane includes the following steps: c1. Mix the PAN / COF composite nanofiber membrane with methanol to obtain a mixture; c2. Add the metal salt corresponding to metal M to the mixture in c1 and continue stirring to obtain a black product; c3. The black product obtained in c2 is washed successively with tetrahydrofuran and methanol, and then dried under vacuum to obtain the PAN / COF@M composite nanofiber membrane.

[0013] Furthermore, in step S4, the preparation of the embedded COF nanofiber aerogel material includes the following steps: d1. Take the PAN / COF@M composite nanofiber membrane, add ultrapure water, and prepare a PAN / COF@M nanofiber dispersion; d2. Dissolve chitosan powder in an aqueous acetic acid solution to obtain a chitosan solution; d3. After mixing the PAN / COF@M nanofiber dispersion obtained in d1 with the chitosan solution obtained in d2, pour the mixture into a mold and freeze-dry it to obtain the embedded COF nanofiber aerogel material.

[0014] Application of embedded COF nanofiber aerogel materials as solar water purification photothermal materials.

[0015] The beneficial effects of this invention are: 1. High surface area and porous structure: Electrospun PAN / TP blend nanofiber membranes have high surface area and adjustable porosity, providing an excellent structural basis for aerogels, which is conducive to water adsorption and rapid transport; 2. High-efficiency photothermal conversion: The black COF (covalent organic framework) material embedded in this invention has excellent light absorption capacity and can achieve high-efficiency solar energy conversion through photothermal effect, thereby improving the evaporation efficiency of water; 3. Catalytic water purification function: The addition of metal ions to complex with COF can endow the aerogel with catalytic water purification function, realizing the degradation and removal of pollutants in the water, thereby achieving a dual water treatment effect; 4. Controllable preparation process: The use of controllable precursor pre-embedding and self-assembly processes ensures high controllability and repeatability in the material preparation process. Electrospinning technology can precisely control the diameter and structure of nanofibers. 5. This invention uniformly loads a COF@M catalyst onto polyacrylonitrile electrospun nanofibers, and then assembles them into a three-dimensional material with capillary water transport capabilities using a short nanofiber assembly method. Its evaporation flux is twice that of ordinary planar evaporation flux, reaching 3.04 kg·m³. -2 ·h -1 It can rapidly degrade volatile organic pollutants in wastewater, which is of great significance for the development of solar distillation water purification technology and for solving the global scarcity of freshwater resources. Attached Figure Description

[0016] Figure 1 This is a schematic diagram of the structure of the PAN / COF@M nanofiber aerogel material of the present invention; Figure 2 This is a scanning electron microscope image of the PAN / COF@Co nanofiber aerogel material prepared in Example 1 of this invention; Figure 3This is a solar light absorption rate test chart of the PAN / COF@Co nanofiber aerogel material prepared in Example 1 of this invention; Figure 4 This is a test graph of the light evaporation flux of the PAN / COF@Co nanofiber aerogel material prepared in Example 1 of this invention; Figure 5 This is an infrared thermal image (top view) of the PAN / COF@Co nanofiber aerogel material prepared in Example 1 of this invention. Figure 6 This is an infrared thermal image (front view) of the PAN / COF@Co nanofiber aerogel material prepared in Example 1 of this invention. Figure 7 This is a test graph showing the catalytic degradation rate of organic matter in wastewater by the PAN / COF@Co nanofiber aerogel material prepared in Example 1 of this invention; Figure 8 This is a diagram showing the VOCs retention effect of the PAN / COF@Co nanofiber aerogel material prepared in Example 1 of this invention.

[0017] Figure 1 The names corresponding to each marker in the text are: 1. PAN / TP electrospun nanofiber aerogel; 2. COF@M catalyst; 3. Pearl cotton foam; 4. Wastewater raw water. Detailed Implementation

[0018] The technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings in the embodiments of the present invention.

[0019] like Figure 1 As shown, the PAN / COF@M nanofiber aerogel material of the present invention includes PAN / TP electrospun nanofiber aerogel 1 and COF@M catalyst 2. The COF@M catalyst 2 is uniformly loaded in the PAN / TP electrospun nanofiber aerogel 1. During the evaporation process of the PAN / COF@M nanofiber aerogel material of the present invention, under the irradiation conditions of a xenon lamp source (simulating a solar source), the prepared PAN / COF@M nanofiber aerogel material is placed in a cut pearl cotton foam, exposed to a suitable height, and placed in a beaker containing raw wastewater. The outer ring of the pearl cotton foam and the edge of the beaker are kept sealed, thereby achieving the purification treatment of the raw wastewater.

[0020] The principle of this invention is as follows: This invention synthesizes a dual-functional PAN / COF@M nanofiber aerogel material, which can not only serve as a photothermal material but also degrade different organic pollutants by selecting different metals (Co, Ti, Zn, Fe, Cu, etc.). Specifically, COF@M catalytic material is in situ loaded onto an electrospun PAN nanofiber membrane, homogenized, and then assembled using a short nanofiber method to prepare a photothermal nanofiber aerogel evaporation column with three-dimensional interfacial evaporation capability. By expanding the evaporation interface and utilizing environmental energy for synergistic evaporation, it can significantly improve water flux, which is of great significance for the development of solar distillation water purification technology and for addressing the global scarcity of freshwater resources.

[0021] Meanwhile, this invention is also an embedded COF nanofiber aerogel material. By uniformly loading the catalytic material into it, it can effectively catalyze the degradation of volatile / semi-volatile organic pollutants. Furthermore, to address the problem of easy detachment of the catalytic material, the COF precursor is added to the spinning solution in advance, so that the subsequent synthesized catalyst is firmly attached to the fiber surface, reducing the risk of detachment. Compared with other catalyst-substrate composite methods, this method not only makes the catalyst firmly embedded in the substrate, but also increases the number of catalytic reaction sites due to the pre-uniform distribution.

[0022] Example 1 Preparation process of PAN / COF@Co photothermal evaporation column: Preparation of S1, Polyacrylonitrile (PAN) / 2,4,6-tricarboxymethyl phloroglucinol (TP) blended nanofiber membrane 1. Weigh 1.7g of polyacrylonitrile (PAN) powder and add it to 10mL of N,N-dimethylformamide (DMF). Place it in a 65℃ water bath and stir until completely dissolved (solution A). 2. Weigh 0.3g of 2,4,6-tricarboxymethyl phloroglucinol (TP) powder and add it to 10mL of DMF. Stir in a 65℃ water bath until completely dissolved (solution B). 3. Mix solution A and solution B and stir at 65°C for one hour, then place the mixture in a spinning machine (operating voltage 15KV, collection distance 25cm, solution flow rate 0.8mL·h). -1 PAN / TP blended nanofiber membranes were obtained by spinning in the process.

[0023] Preparation of S2, PAN / COF composite nanofiber membranes 1. Weigh 420 mg of PAN / TP membrane into a 10 mL Schlenk tube, then add 0.45 mmol of 2,5-diaminohydroquinone hydrochloride (Pa-(OH)2·2HCl) powder, 12 mL of a mixed solution of dioxane and trimethylbenzene (volume ratio 1:1), and 2 mL of 6 M acetic acid; 2. After sonicating the mixture for 30 minutes, the Schlenk tube was placed in liquid nitrogen for freezing-evacuation-thawing, and the oxygen was removed by three cycles. The reaction tube was then vacuum-sealed and placed in an oven at 120°C for 2 days. 3. Wash the product obtained from the reaction sequentially with tetrahydrofuran, water, and acetone, and dry it under vacuum at 50°C overnight.

[0024] Preparation of S3, PAN / COF@Co composite nanofiber membranes 1. Weigh 258 mg of dried composite fiber membrane and add it to 40 mL of methanol, stirring for 4 hours; 2. Add 800 mg of cobalt nitrate hexahydrate to the mixture and stir the mixture at room temperature for 12 hours. 3. The obtained black product was washed successively with tetrahydrofuran and methanol, and then dried under vacuum at 45°C for 12 hours.

[0025] Preparation of S4, PAN / COF@Co photothermal evaporation column 1. Weigh 120 mg of PAN / COF@Co composite nanofiber membrane, add 20 mL of ultrapure water and break it up to prepare an electrospinning concentration of 6 mg / mL. -1 The dispersion; 2. Weigh 1g of chitosan powder and dissolve it in 50mL of 2% acetic acid aqueous solution to prepare a 1% concentration chitosan solution; 3. The obtained PAN / COF@Co composite nanofiber membrane dispersion and chitosan solution were mixed at a mass ratio of 8:1. After stirring evenly, the cross-linked nanofiber dispersion was poured into a square copper tube (2cm×2cm×5cm), frozen in a refrigerator for 12 hours, and then freeze-dried for 36 hours to obtain PAN / COF@Co nanofiber aerogel material (i.e., PAN / COF@Co photothermal evaporation column).

[0026] The performance of the product prepared in this embodiment was investigated and analyzed: The PAN / COF@Co nanofiber aerogel material prepared in this embodiment was scanned using a scanning electron microscope to obtain images of the sample surface, such as... Figure 2 As shown, the PAN / COF@Co nanofiber aerogel material prepared by this invention has a significantly rough surface, with some connection points between the fibers. The fibers are tightly attached to each other, which can provide active sites for the components and has good catalytic performance.

[0027] The solar light absorption rate of the PAN / COF@Co nanofiber aerogel material prepared in this embodiment was tested in the wavelength range of 200~2000nm, and the results are as follows. Figure 3As shown, the PAN / COF@Co nanofiber aerogel material of this invention has an absorbance of 95% in the wavelength range of 200nm~760nm, exhibiting excellent visible light absorption performance, which is a prerequisite for ensuring solar distillation water purification.

[0028] An evaporation flux measurement experiment was conducted on the PAN / COF@Co nanofiber aerogel material (extending 3 cm beyond pearl cotton foam) prepared in this embodiment and a conventional PAN / COF@Co nanofiber plane. A xenon lamp was used to simulate a solar energy source, and the weight of water lost during evaporation was accurately displayed and recorded using a 1 / 2 ppm balance. The results are as follows. Figure 4 As shown; it can be seen that in a simulated solar intensity (1 kW·m²), -2 Under irradiation, the planar evaporation flux of PAN / COF@Co is 1.46 kg·m. -2 ·h -1 The evaporation flux of the PAN / COF@Co photothermal evaporation column can reach 3.04 kg·m³. -2 ·h -1 The evaporation flux has more than doubled, which is of great significance for the development of solar distillation water purification technology and for solving the global scarcity of freshwater resources.

[0029] Simultaneously, the surface temperature of the evaporation column was measured in the evaporation flux measurement experiment. Under simulated solar intensity irradiation, the surface temperature of the PAN / COF@Co photothermal evaporation column of this invention increased from 17.6℃ to 40.1℃, indicating that COF@Co has excellent photothermal conversion capabilities. Meanwhile, the side temperature of the column decreased from 17.6℃ to 16℃. Although the side can hardly absorb solar energy, the enthalpy of water evaporation keeps the side temperature lower than the surrounding environment temperature, thus obtaining energy from the environment in the form of thermal convection and thermal radiation, achieving a higher level of evaporation. This invention can be used in various ways (see...). Figure 1 , 5 (6) provides evidence that the three-dimensional structure of this invention can utilize not only solar energy but also thermal energy in space to achieve high-throughput evaporation.

[0030] The PAN / COF@Co photothermal evaporation column prepared in this embodiment was used for catalytic degradation experiments of organic matter and retention experiments of volatile organic compounds (VOCs). The results are as follows: Figure 7-8 As shown.

[0031] like Figure 7 As shown, the concentration of methylene blue is 20 mg·L⁻¹. -1 The dosage of potassium persulfate is 400 mg·L⁻¹. -1Within 40 minutes of initial adsorption equilibrium, the PAN / TP aerogel achieved an adsorption efficiency of 10% for MB, while the PAN / COF@Co nanofiber composite aerogel material achieved 38%. After adding the oxidant PMS, the degradation efficiencies of PAN / TP and PAN / COF@Co nanofiber composite aerogel materials reached 13% and 92% respectively within 5 minutes. This indicates that the present invention has a strong catalytic effect on the degradation of organic matter in wastewater.

[0032] In the volatile organic compound (VOC) retention experiment, phenol was used as a marker VOC. The concentration of phenol in the raw water was 10 mg / L, and the resulting distilled water was tested. Figure 8 As shown, no phenol was detected in the distilled water, indicating that the PAN / COF@Co nanofiber aerogel material of the present invention has a strong interception and degradation effect on volatile organic compounds (VOCs), which can effectively ensure the safety of purified water.

[0033] This invention is not limited to the preferred embodiments described above. Anyone can derive other forms of products under the guidance of this invention. However, regardless of any changes made in their shape or structure, any technical solution that is the same as or similar to this application falls within the protection scope of this invention.

Claims

1. An embedded COF nanofiber aerogel material, characterized in that: It includes PAN / TP electrospun nanofiber aerogel and COF@M catalyst, with the COF@M catalyst uniformly loaded in the PAN / TP electrospun nanofiber aerogel.

2. The embedded COF nanofiber aerogel material according to claim 1, characterized in that: In the COF@M catalyst, the metal M includes Co, Ti, Zn, Fe, and Cu.

3. The method for preparing the embedded COF nanofiber aerogel material according to any one of claims 1-2, characterized in that, Includes the following steps: S1. Electrospinning to prepare PAN / TP blended nanofiber membranes; S2. The PAN / TP blended nanofiber membrane prepared in S1 is mixed and reacted with the COF precursor, and COF is grown in situ on the PAN / TP blended nanofiber membrane to obtain the PAN / COF composite nanofiber membrane. S3. React the PAN / COF composite nanofiber membrane prepared in S2 with metal ions to obtain the PAN / COF@M composite nanofiber membrane. S4. After mixing the PAN / COF@M composite nanofiber membrane obtained in S3 with the chitosan solution evenly, pour it into a mold and freeze-dry it to obtain the embedded COF nanofiber aerogel material of the present invention.

4. The method for preparing the embedded COF nanofiber aerogel material according to claim 3, characterized in that, In step S1, the preparation of the PAN / TP blend nanofiber membrane includes the following steps: a1. Dissolve polyacrylonitrile (PAN) in N,N-dimethylformamide (DMF) to obtain solution A; a2. Dissolve 2,4,6-tricarboxymethylphloroglucinol TP in N,N-dimethylformamide DMF to obtain solution B; a3. After thoroughly mixing solution A and solution B, place them in a spinning machine to spin PAN / TP blended nanofiber membranes.

5. The method for preparing the embedded COF nanofiber aerogel material according to claim 3, characterized in that, In step S2, the preparation of the PAN / COF composite nanofiber membrane includes the following steps: b1. Mix PAN / TP film, 2,5-diaminohydroquinone hydrochloride powder, dioxane and trimethylbenzene mixed solution and acetic acid to obtain a mixture; b2. After ultrasonic treatment of the b1 mixture, place it in liquid nitrogen to remove oxygen, and then seal it under vacuum for reaction. b3. The product obtained from reaction b2 is washed sequentially with tetrahydrofuran, water, and acetone, and then dried under vacuum to obtain the PAN / COF composite nanofiber membrane.

6. The method for preparing the embedded COF nanofiber aerogel material according to claim 5, characterized in that: In the aforementioned mixed solution of dioxane and trimethylbenzene, the volume ratio of dioxane to trimethylbenzene is 1:

1.

7. The method for preparing the embedded COF nanofiber aerogel material according to claim 3, characterized in that, In step S3, the preparation of the PAN / COF@M composite nanofiber membrane includes the following steps: c1. Mix the PAN / COF composite nanofiber membrane with methanol to obtain a mixture; c2. Add the metal salt corresponding to metal M to the mixture in c1 and continue stirring to obtain a black product; c3. The black product obtained in c2 is washed successively with tetrahydrofuran and methanol, and then dried under vacuum to obtain the PAN / COF@M composite nanofiber membrane.

8. The method for preparing the embedded COF nanofiber aerogel material according to claim 3, characterized in that, In step S4, the preparation of the embedded COF nanofiber aerogel material includes the following steps: d1. Take the PAN / COF@M composite nanofiber membrane, add ultrapure water, and prepare a PAN / COF@M nanofiber dispersion; d2. Dissolve chitosan powder in an aqueous acetic acid solution to obtain a chitosan solution; d3. After mixing the PAN / COF@M nanofiber dispersion obtained in d1 with the chitosan solution obtained in d2, pour the mixture into a mold and freeze-dry it to obtain the embedded COF nanofiber aerogel material.

9. The application of the embedded COF nanofiber aerogel material according to any one of claims 1-8 as a solar water purification photothermal material.